2021
DOI: 10.1371/journal.pone.0251115
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to cardiovascular pharmacotherapy by patients in Iraq: A mixed methods assessment using quantitative dried blood spot analysis and the 8-item Morisky Medication Adherence Scale

Abstract: This study evaluated the adherence to prescribed cardiovascular therapy medications among cardiovascular disease patients attending clinics in Misan, Amara, Iraq. Mixed methods were used to assess medication adherence comprising the Arabic version of the eight-item Morisky Medication Adherence Scale (MMAS-8) and determination of drug concentrations in patient dried blood spot (DBS) samples by liquid chromatography-high resolution mass spectrometry. Three hundred and three Iraqi patients (median age 53 years, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
2
5
1
1
Order By: Relevance
“…In Ethiopia, a study by Shimels et al reported an even lower figure for diabetic and hypertensive patients during the COVID-19 epidemic with only 28% adherence [ 28 ]. In contrast, the percentage of patients’ adherence in our study was lower than in an earlier study in Iraq that determined adherence based on a questionnaire (81.8%) [ 29 ]. However, most published studies on medication adherence in CVD patients used the eight-item Morisky Medication Adherence Scale (MMAS-8) questionnaire, which is distinct from the GMAS questionnaire we used since it does not mention the economic factors affecting adherence.…”
Section: Discussioncontrasting
confidence: 99%
“…In Ethiopia, a study by Shimels et al reported an even lower figure for diabetic and hypertensive patients during the COVID-19 epidemic with only 28% adherence [ 28 ]. In contrast, the percentage of patients’ adherence in our study was lower than in an earlier study in Iraq that determined adherence based on a questionnaire (81.8%) [ 29 ]. However, most published studies on medication adherence in CVD patients used the eight-item Morisky Medication Adherence Scale (MMAS-8) questionnaire, which is distinct from the GMAS questionnaire we used since it does not mention the economic factors affecting adherence.…”
Section: Discussioncontrasting
confidence: 99%
“…The total score ranges from −0-33, a higher score indicating a high adherence level. The final score is stratified into five groups; high (30)(31)(32)(33), good (27)(28)(29), partial (17)(18)(19)(20)(21)(22)(23)(24)(25)(26), low (11)(12)(13)(14)(15)(16), and poor (≤10). Prior to conducting this study, permission to use the tool was obtained.…”
Section: Instrumentmentioning
confidence: 99%
“…Self-reported medication adherence questionnaires are one of the acceptable tools. 11 In Saudi Arabia, Morisky's Medication Adherence Scale (MMAS) and General Medication Adherence Scale (GMAS) are common validated instruments used for assessing medication adherence. 12 GMAS is considered more sensitive, specific, and accurate than MMAS.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, pill counts simply confirm the number of tablets removed from their original container but cannot corroborate if these tablets have actually been consumed by the patient. Although questionnaire tools are widely used, they are subjective as the evaluation is dependent on the participant's belief and recall bias [18]. Furthermore, this indirect adherence assessment strategy provides no information about the time a dose was taken and is unable to take into consideration drug pharmacokinetics and pharmacodynamics which vary from patient to patient and which may be fundamental in establishing clinical outcomes [6].…”
Section: Plos Onementioning
confidence: 99%